Assessment of Quality of Life and Treatment Adherence in Patients under Maintenance Hemodialysis: A Cross- Sectional Study - Thapa, Dejina; Koirala, Pooja; Chaulagain, Durga; Kafle, Tara; Belbase, Deepak; Bhagat, Subhadra (Birat Journal of Health Sciences, 2021)
Introduction: Chronic Kidney Disease causes sudden changes in the daily lives of patients and creates a great impact on their quality of life. Failure of adherence in Hemodialysis can lead to increased morbidity, mortality, cost, and burden on health care system. Objectives: This study was conducted to assess the quality of life and adherence to treatment of patients undergoing Hemodialysis. Methodology: A descriptive correlational study was carried out at Nobel Medical College Teaching Hospital, Biratnagar, among 96 patients who were under HD using convenience sampling technique. The data was collected through face to face interview for the period of 5 months. Quality of life and adherence to treatment were assessed using Kidney Disease Quality of Life Questionnaire (KDQOL) and End Stage Renal Disease Adherence Questionnaire (ESRD – AQ) respectively. The data was analyzed using t test, Spearman correlation statistics. Results In this study, the overall mean score of quality of life (QOL) of patients under HD was 48.9±13.7. More than half (54.1%) of the patients had moderate adherence to treatment while 31.2% had good adherence. Domains with the highest and lowest scores on quality of life and adherence to treatment were social domain and illness impact and adherence to HD treatment and diet restriction, respectively. There was statistically significant association between total score of quality of life and duration of HD (p≤0.05). Likewise, there was statistically significant association between adherence to treatment and marital status (p≤0.05), educational status (p≤0.05), ethnicity (p≤0.05), duration of illness (p≤0.05). Poor correlation (r= 0.273) was observed between quality of life and adherence to treatment. Conclusion: On average, the kidney disease component dimension of quality of life of patients under HD is higher and the overall level of adherence to treatment was moderate. Thus proper periodic counseling on illness and its long term impact, regular follow up as well as information on adherance to dietary measures are important to improve the quality of life and treatment adherance of patients under hemodialysis.